2009
DOI: 10.1016/j.jembe.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen limited thermal tolerance and performance in the lugworm Arenicola marina: A latitudinal comparison

Abstract: Global warming trends in the marine environment currently lead to poleward shifts in the distribution of marine fauna along European coastlines indicating limited thermal tolerance of affected species and potential loss of their southernmost populations. The present study analyses the degree and limits of thermal specialisation in various populations of a key species of the intertidal zone, the lugworm Arenicola marina, which is exposed to highly fluctuating conditions in temperature, salinity, pH and oxygen l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Wittmann et al (2008) and Schröer et al (2009) demonstrated such shifts in the intertidal lugworm Arenicola marina according to season and climate zone. Such acclimatization capacity is reflected in the up-regulation of metabolic capacity upon cold exposure and the down-regulation of metabolic costs in warm conditions, such that residual aerobic scope remains sufficiently high.…”
Section: Coastal and Intertidal Invertebratesmentioning
confidence: 97%
“…Wittmann et al (2008) and Schröer et al (2009) demonstrated such shifts in the intertidal lugworm Arenicola marina according to season and climate zone. Such acclimatization capacity is reflected in the up-regulation of metabolic capacity upon cold exposure and the down-regulation of metabolic costs in warm conditions, such that residual aerobic scope remains sufficiently high.…”
Section: Coastal and Intertidal Invertebratesmentioning
confidence: 97%
“…mitochondria, enzymes, ion and gas transport capacities as well as membrane composition (Hazel, 1995;Willmer et al, 2000;Hochachka and Somero, 2002). Thus, seasonal acclimatization or laboratory acclimation to different temperatures shifts the thermal tolerance windows in invertebrates and fish due to the readjustment of energy metabolism (Sommer et al, 1997;van Dijk et al, 1999;Pörtner, 2002;Sommer and Pörtner, 2002;Sokolova and Pörtner, 2003;Wittmann et al, 2008;Schröer et al, 2009). Similarly, long-term acclimation to changing salinity in aquatic invertebrates and fish often involves metabolic readjustments to reduce SMR and/or preserve the aerobic scope except when salinity change is extreme (Shumway and Koehn, 1982;Nelson et al, 1996;Sangiao-Alvarellos et al, 2005;Kidder et al, 2006).…”
Section: Basics Of Energy Balance In Animalsmentioning
confidence: 99%
“…Such levels decrease toward thermal extremes and can therefore be adopted as proxies of aerobic scope. Increased ventilation in vertebrates, like Gadus morhua (Sartoris et al, 2003) and Pachycara brachycephalum (Mark et al, 2002), and invertebrates, such as Maja squinado (Frederich and Pörtner, 2000), Sepia officinalis (Melzner et al, 2006a,b) and Arenicola marina (Schröer et al, 2009) contributes to sustain aerobic scope. Similarly, increased cardiac frequency in fish (Heath and Hughes, 1973; Mark et al, 2002; Farrell, 2009; Farrell et al, 2009) and, in combination with variations of stroke volume, in crustaceans (Spaargaren, 1974; Frederich and Pörtner, 2000; Walther et al, 2009), maintains oxygen delivery to tissues when demand increases but, in turn also contributes to the demand.…”
Section: Introductionmentioning
confidence: 99%